The Woman Detective: Gender & Genre - Klein, Kathleen Gregory (University of Illinois Press, 1995)
Kathleen Gregory Klein traces female paid, professional private investigators in British, Canadian, and American novels, revealing that the detective novel is both a reflection of and potential barrier to social change for women. This edition adds sixty new female private eyes to the roster and includes an afterword that assesses the current state of the genre's new and old novels. A comprehensive bibliography and a character list update the field through mid-1994.--(Source of description unspecified.)
Keywords: Detective and mystery stories, English; English-speaking countries; History and criticism; Detective and mystery stories, American; History and criticism; Popular literature; History and criticism; Women detectives in literature; Women in literature; dept.eng; faculty_collection